Bioprospecting novel cellulose-degrading enzymes from pome metagenomic DNA libraries by enrichment strategy - Ben Belgacem, Farah Fadwa; Bellag, Oualid Abdel Kader; Noor Batcha, Ibrahim Ali; Mohd Salleh , Hamzah (Kulliyah of Engineering, International Islamic University Malaysia, 2016)
Green technology is the environment-friendly way to protect the Earth’s natural resources and the environment we inhabit. The functionalmetagenomic approach has proven to be a powerful tool to identify novel biocatalysts indispensables in green technology of biofuel production from plant’s biomass through metagenomic DNA library construction and high-throughput screening. Culture enrichment strategies are additional pre-screening methods to provide an attractive mean of enhancing the screening hit rate. In this work metagenomic DNA libraries were made from Malaysian palm oil mill effluent (POME) microorganisms after culture enrichment experiment based on natural selection principle. Metagenomic DNA was extracted from both enriched and non-enriched cultures and cloned to pCC1FOS fosmid and transformed into EPI300™-T1RE. coli.Qualitative and quantitative analysis of metagenomic DNA and recombinant clones are provided to confirm the efficiency of enrichment strategy.